Thinking misprints: a reading of Pedro e Paula, by Helder Machado - Dantas, Gregório F. (Literatura e Sociedade, 2010)
The present essay intends to undertake a reading of Pedro e Paula, the novel by the Portuguese author Helder Macedo, takinginto account the appropriation of intertextual references of Machado de Assis’ works. Thus, we intend to interpret Pedro e Paula from the criteria adopted by the very author to interpret the fictional works of his election, Machado de Assis included.